Two new species of Diamphipnoidae (Insecta: Plecoptera) from Chile, with description of adults and eggs - Sánchez, Alejandro Vera (Zootaxa, 2018)
Two new species of the Plecoptera family Diamphipnoidae are described from Chile. Illustrations of the details of the male genitalia, female genitalia, and eggs are provided for these two new taxa. Diamphipnoa fresiae sp. nov. has the lowest latitudinal distribution of the genus in South America and the male is the smallest known for the family and has also unusual wing venation. Diamphipnopsis oncolensis sp. nov., also a small species is known only from the Parque Oncol, south of Valdivia, Chile. This species is characterized by its distinctive abdominal coloration pattern in both sexes of the adult. Additionally, the large diameter of the eggs and the prominent tubercles of the chorion characterize this new species.